2015
DOI: 10.1371/journal.pone.0130462
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Atherosclerosis in Patients with Rheumatoid Arthritis and Low Cardiovascular Risk: The Role of von Willebrand Factor Activity

Abstract: BackgroundTo evaluate association between von Willebrand factor (vWF) activity, inflammation markers, disease activity, and subclinical atherosclerosis in patients with rheumatoid arthritis (RA) and low cardiovascular risk.MethodsAbove mentioned parameters were determined in blood samples of 74 non-diabetic, normotensive, female subjects, with no dyslipidemia(42 patients, 32 matched healthy controls, age 45.3±10.0 vs. 45.2±9.8 years). Intima-media thickness (IMT) was measured bilaterally, at common carotid, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Recent quantities clinical observations have confirmed that RA is associated with increased CIMT [ 96 - 99 ]. The mechanisms of RA-related CIM thickening included increased levels of Ox-LDL) [ 100 , 101 ], vWF activity [ 102 ], serum mannose-binding lectin [ 103 ], and PWV [ 104 ] as well as increased levels of inflammation markers [ 99 , 102 ] such as IL-17 [ 105 ], and CRP [ 106 ] and lower levels of β-carotene [ 101 ], vitamin D, CD34+ cells [ 100 , 104 ] and NO [ 101 ]. Psoriasis is associated with increased mean CIMT [ 107 ] and may increase the burden of subclinical atherosclerosis [ 107 , 106 ].…”
Section: The Associations Between Cimt and Novel Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent quantities clinical observations have confirmed that RA is associated with increased CIMT [ 96 - 99 ]. The mechanisms of RA-related CIM thickening included increased levels of Ox-LDL) [ 100 , 101 ], vWF activity [ 102 ], serum mannose-binding lectin [ 103 ], and PWV [ 104 ] as well as increased levels of inflammation markers [ 99 , 102 ] such as IL-17 [ 105 ], and CRP [ 106 ] and lower levels of β-carotene [ 101 ], vitamin D, CD34+ cells [ 100 , 104 ] and NO [ 101 ]. Psoriasis is associated with increased mean CIMT [ 107 ] and may increase the burden of subclinical atherosclerosis [ 107 , 106 ].…”
Section: The Associations Between Cimt and Novel Risk Factorsmentioning
confidence: 99%
“…More severe subclinical atherosclerosis was observed in patients with PsA [ 108 ] compared with patients with cutaneous psoriasis without arthritis (PsC). The causes of atherosclerosis in PsA include markers of accelerated atherosclerosis such as ox-LDLs and NO [ 101 ] as well as endothelial dysfunction [ 106 ], PsA disease duration, more severe skin disease and increased inflammatory markers; however, atherosclerosis in PsA was not associated with traditional CV risk factors [ 108 ]. Furthermore, increased CIMT was associated with juvenile idiopathic arthritis [ 109 ], systemic lupus erythematosus [ 110 ], and BD [ 111 ].…”
Section: The Associations Between Cimt and Novel Risk Factorsmentioning
confidence: 99%
“… 38 42 Common carotid artery IMT shows positive correlations with the duration of inflammatory articular disease, laboratory parameters reflecting inflammation, age, and traditional risk factors for cardiovascular disease. 43 46 Cardiology societies suggest that evaluation of common carotid artery IMT should form part of the medical assessment of patients at increased cardiovascular risk, 40 and rheumatology guidelines recommend that patients with inflammatory arthritis should undergo ultrasound evaluation of the carotid arteries. 47 Evaluation of these criteria in arthritis was established based on histologic evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-inflammatory medications do not eradicate irreversible changes, but decrease further arterial stiffness progression. Rheumatoid Factor positivity is associated with more morphological changes in the vasculature [ 20 , 32 ]. A study headed by Laura Geraldino-Pardilla used F-Fluorodeoxyglucose positron emission tomography/computed tomography (F-FDG-PET/CT) to detect ascending aorta inflammation [ 7 ].…”
Section: Reviewmentioning
confidence: 99%